Analysis of genetic diversity of the Thai swamp buffalo (Bubalus bubalis) using cattle microsatellite DNA markers - K. Triwitayakorn (2018)
Recently the numbers of the Thai swamp buffalo (Bubalus bubalis), a native species of Thailand, have been rapidly declining, leading to a requirement for conservation programs for this breed. Such studies of the genetic diversity of this species are essential for conservation decisions and to assist the rational implementation of breeding programs. In this study, the genetic diversity of 80 Thai swamp buffalo, randomly selected from seven different research stations of the Thai Department of Livestock Development, were studied using ten cattle microsatellite markers. Polymorphic PCR products were observed at all microsatellite loci, with percentages of polymorphic loci ranging from 80.00 to 100.00%. The population from Payao showed the lowest level of polymorphism. The mean number of alleles per locus was 4.7 with the highest number of alleles being eight (ETH152) and the lowest being three (HAUT27 and ILSTS030). The average unbiased heterozygosity for all seven populations was 0.61 and varied between 0.5314 (Samui) and 0.6798 (Surin). The genetic distance according to NEI's (1972) ranged from 0.0722 to 0.4427. The populations from Surin and Burirum are the closest populations, while populations from Samui and Payao are the most divergent. The information generated by this study will greatly aid in the establishment of effective breeding and conservation programs for the Thai swamp buffalo.